Role of Nuclear Factor (Erythroid-Derived 2)-Like 2 Signaling for Effects of Fumaric Acid Esters on Dendritic Cells - Hammer, Anna; Waschbisch, Anne; Knippertz, Ilka; Zinser, Elisabeth; Berg, Johannes; Jörg, Stefanie; Kuhbandner, Kristina; David, Christina; Pi, Jingbo; Bayas, Antonios; Lee, De-Hyung; Haghikia, Aiden; et al. (Frontiers in Immunology, 2017)
To date, the intracellular signaling pathways involved in dendritic cell function are poorly understood. The anti-oxidative transcription factor nuclear factor (erythroid-derived 2)-like 2 (Nrf2) has been shown to affect maturation, function, and subsequent dendritic cell-mediated T cell responses of murine and human dendritic cells. In experimental autoimmune encephalomyelitis, as prototype animal model for a T helper cell mediated autoimmune disease, antigen presentation, cytokine production and costimulation by dendritic cells play a major role. We explore the role of Nrf2 in dendritic cell function, and dendritic cell-mediated T cell responses during T cell mediated autoimmunity of the central nervous system using genetic ablation and pharmacological activation in mice and men to corroborate our data in a translational setting. In murine and human dendritic cells, monomethyl fumarate induced Nrf2 signaling inhibits dendritic cell maturation and dendritic cell-mediated T cell proliferation by reducing inflammatory cytokine production and expression of costimulatory molecules. In contrast, Nrf2-deficient dendritic cells generate more activated T helper cells (Th1/Th17) but fewer regulatory T cells and foster T cell proliferation. Transfer of dendritic cells with Nrf2 activation during active experimental autoimmune encephalomyelitis reduces disease severity and T cell infiltration. Our data demonstrate that Nrf2 signaling modulates autoimmunity in murine and human systems via inhibiting dendritic cell maturation and function thus shedding further light on the mechanism of action of antioxidative stress pathways in antigen presenting cells.